Kinetics of Nutrient Removal in an Integrated Suspended Growth Reactor - Yahya Almahbashi, Najib Mohammed (International Journal of Integrated Engineering, 2019)
Wastewater effluent discharge in a large amount of ammonia, nitrate and phosphorus lead to eutrophication the river. Eutrophication is a serious environmental issue that threaten the fishes and aquatic plants. To prevent this from happening, ammonia produced in STP and raw wastewater removal is achieved during nitrification by having an extended aeration while nitrate removal is achieved during denitrification in anoxic tank. In this research study, a pilot plant of integrated suspended growth system (i-SGS) reactor was used to achieve simultaneous removal of ammonia and nitrate. The reactor has three main compartments which are anoxic chamber, aeration camber, and clarifier and operated at a constant flow rate of 720 L/d and fixed SRT of 40 days. The RAS time was set to once every 10 minutes for 5 minutes while the IR time is once every 16 minutes for 5 minutes. The wastewater quality parameters, namely chemical oxygen demand (COD), ammonia, and nitrate were measured to determine and evaluate the removal efficiency of them in i-SGS whereas phosphorus was measured to ensure the effluent standard meet the C:N:P ratio requirement. Samples from four sampling points were taken to conduct the laboratory experiment and three replication of the results for each parameter were measured. It was determined that i-SGS was able to eliminate average 72% of COD at 46 mg/L of clarifier effluent, and achieved 95% of ammonia removal at average 1.22 mg/L of the clarifier effluent concentration while obtained 43% of nitrate removal in the anoxic tank. Last but not least, the C:N:P ratio obtained was 100:14:8, denoted that i-SGS has ample of nutrients loading provided because it is more than the minimum nutrient requirements, 100:5:1. The removal was possible through the nitrification-denitrification process in the i-SGS pilot plant bioreactor. The operational SRT of 40 days have shown to be effective and stable for the COD but not for nitrifiers. The effluent discharge of COD, ammonia and nitrate in the pilot plant i-SGS has meet the standard requirement of DOE Malaysia, standard A and B respectively.